A discrepancy between CT angiography and transesophageal echocardiographic measurements of the annular size affect long-term survival following trans-catheter aortic valve replacement - Siddarth Singh; Piotr S. Rutkowski; Alexey Dyachkov; Vijay S. Iyer; Leili Pourafkari; Nader D. Nader (Journal of Cardiovascular and Thoracic Research, 2021)
Introduction: Accurate measurement of the aortic valve annulus is critical for proper valve sizing for the transcatheter aortic valve replacement (TAVR) procedure. While computed tomography angiography (CTA) is the widely-accepted standard, two-dimensional (2D) and three-dimensional(3D) transesophageal echocardiography (TEE) is commonly performed to measure the size of the aortic valve and to verify appropriate seating of prostheses. Methods: Patients undergoing TAVR between 2013-2015 were examined. 2D- and 3D-TEEmeasurements were compared to CTA taken as standard. Patients were followed for at least one year. The presence and effect of discrepancy (defined as a difference of more than 10%) between CTA and TEE measurements on survival were examined. Results: One hundred eighty-five patients (70 men) were included. 2D- and 3D-TEE measurements underestimated the annulus size by -1.49 and -1.32 mm, respectively. Discrepancies > 10% between TEE and CTA methods in estimating the aortic annulus size were associated with a decrease in post implant survival. The peak pressure gradient across the aortic prosthesis measured one year after the implant was higher in patients with an initial discrepancy between 3D-TEE and CTA measurements. In a multivariate cox-regression model, the discrepancy between CTA and 2D-TEE readings and the smaller size of the aortic annular area were the predictors of long-term survival. Conclusion: Both 2D and 3D-TEE underestimate the aortic annulus measurements compared to CTA, with 2D-TEE being relatively more precise than 3D-TEE technology. The presence of a discrepancy between echocardiographic and CTA measurements of the aortic annulus is associated with a lower survival rate.